How to Use Your Turbo Trainer - Firth, M. (2001)
Midweek quality training needs to be done during the winter months if you want the standard of your racing to improve each year, and the ideal place to do it is on your turbo trainer. Indoors on your trainer you don't have to worry that it is dark outside, or that the weather may be bad, or that the roads are busy. Instead, you can get on with your essential high quality bike training, without your concentration being constantly interrupted. At this time of year these turbo training sessions will be more productive than trying to get out on the local chain gang, and a good deal warmer too! Planned properly, turbo training can give your enthusiasm a boost and help you through this vital stage in your preparation. Turbo training is also useful during the summer months when you may want to do interval training. It allows you to do so without the need to find reasonably flat, traffic-free roads. You don't even have the need to remember the session, you can pin it up on the wall near you as a constant reminder of what comes next.